Review of innovative proposals for mobility in public transportation in Latin America for the transformation to sustainable smart cities (Publicaciones en Ciencias y Tecnología, 2020)
Latin America is a highly urbanized region with almost 80% of the population living in cities. The design of traditional cities is giving way to the design of smart and sustainable cities, which are recognized for the use of information and communication technologies. There are various actors that are supporting the development of innovation projects and the adoption of cleaner technologies in transportation. In this paper various proposals on sustainable mobility as a contribution to the transformation towards smart cities are reviewed, as well as the thematic areas of associated innovation and applications in innovation projects, among which electric buses, electric bicycles, shared transport, stand out, cable cars and mobile applications, as well as transport models under the Mobility as a Service (MaaS) phenomenon. The efforts in Latin America for the transformation of urban mobility by various actors from the public and private sectors contribute positively to the development of cities in the region.
Keywords: smart sustainable cities; sustainable transport; innovation; sustainable movility; Latin America